Adjudicação - Menin, Gilberto Leme (2011)
This dissertation aims to the studies of adjudication in the execution action of extrajudicial and fulfillment of sentence, especially from the strength of the Federal Law 11,382/2006, which lifted the institute of preferential expropriation technique. The choice of topic was given by the fact that few authors have discoursed profoundly on the subject. That aim was achieved through literature review, material collected during the collection of realized credits, research of legislation and jurisprudence. Began working from the historical origin of the adjudication of the Roman law, passing its application to Portuguese law and the Codes of Civil Procedure, the prior and current legislation and strength of legislation. Finally, we have made observations and suggestions to the project of the new Code of Civil Procedure